Prevalence of surgical site infection in patient with bile spillage during laparoscopic cholecystectomy - Parajuli, Anuj (Journal of Society of Surgeons of Nepal, 2020)
Introduction: Iatrogenic gallbladder perforation with bile spillage (BS) during laparoscopic cholecystectomy (LC) occurs frequently but its impact to the patient can range from port site surgical site infection (SSI), bowel obstruction, intraperitoneal abscess to none. We aim to examine the prevalence of port site SSI in patients with bile spillage during laparoscopic cholecystectomy. Methods: A prospective descriptive cross-sectional study was undertaken which included consecutive patients who underwent LC over a period of six months and had intraoperative bile spillage. Patients were noted and evaluated for the presence of port site SSI. Patients were assessed clinically during hospitalization and on follow-up at five and even days post operatively. Bile spillage (BS) as a possible risk factor for port site surgical site infection (SSI) was analyzed. Results: Out of 318 patients, there were 229 (72%) female and 89(28%) male patients with a mean age of 46 ± 11.7 years. BS occurred in 66 (20.8%) patients. Port site SSI was present in 14 (4.4%) patients. SSI among patients with bile spillage was present in 8 (12.1%) and among patients without BS was 6 (2.3%). Conclusion: The present study reveals that iatrogenic gallbladder perforation with BS has higher prevalence of port site SSI.